Exchange Rates and Domestic Credit-Can Macroprudential Policy Reduce the Link? - Nier, Erlend (IMF Working Papers; Working Paper ;, 2020)
This paper examines empirically the role of macroprudential policy in addressing the effects of external shocks on financial stability. In a sample of 62 economies over the period of 2000: Q1-2016: Q4, our dynamic panel regressions show that an appreciation of the local exchange rate is associated with a subsequent increase in the domestic credit gap, while a prior tightening of macroprudential policies dampens this effect. These results are strong for small open economies, and robust when we explicitly account for potential simultaneity and reverse causality biases. We also examine a feedback effect where strong domestic credit pulls in additional cross-border funding, potentially further increasing systemic risk, and find that targeted capital controls can play a complementary role in alleviating this effect.